Yayasan Sebagai Entitas Hukum Dalam Konteks Perdagangan Yayasan Aksi Cepat Tanggap dan Dampaknya Terhadap Mitra Bisnis di Indonesia - Stevani, Frisca Adelia; Silalahi, Riovaldi Paruntungan; Sembiring, Nirindah Daniella; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Foundation is a legal entity recognized in the Indonesian legal system, with the main purpose of conducting activities in the social, humanitarian and religious fields. Although foundations are not profit-oriented entities, laws and regulations provide opportunities for foundations to own and run businesses, provided that all profits are used to achieve the foundation's objectives. However, problems arise when foundations abuse their position and status, such as what happened to the Aksi Cepat Tanggap (ACT) Foundation, which stumbled upon a scandal of misuse of public funds. This case had a significant impact on the business ecosystem in Indonesia, especially business partners affiliated with the foundation. This article aims to examine the role of foundations in the context of commercial law in Indonesia, particularly by highlighting the legal aspects governing foundations as non-profit entities engaged in commercial activities. The case study of ACT Foundation is used to analyze the impact of the scandal on its business partners, including aspects of trust, reputation, as well as corporate social responsibility (CSR). In addition, this article also discusses the importance of implementing good foundation governance, such as transparency and accountability, in collaborating with the business sector. With a multidisciplinary approach that includes legal, economic, and management perspectives, this article provides a comprehensive overview of how a foundation can affect its business partners when governance violations occur, as well as the legal implications in the context of trade in Indonesia.